Emotional Artificial Intelligence and Brand Association: A Neuro-Bibliometric Study - Rachman, Adryan; Karina Diandra, Prita; Simon, Febryanti (Asosiasi Ahli Administrasi Indonesia, 2024)
This study conducts a comprehensive bibliometric analysis to explore the research landscape in neuromarketing and brand association. With a growing interest in the neural mechanisms influencing consumer behavior, neuromarketing leverages neuroscientific techniques like fMRI, EEG, and eye tracking to uncover subconscious decision-making processes. The study aims to map research trends, identify key themes, and highlight influential works within this field. Using data from Scopus and Web of Science, the methodology includes examining publication growth, geographic distribution, co-authorship networks, and keyword co-occurrence over the past two decades. The data collection process employed effective keywords such as